Influência nas características do escoamento em função da alteração da geometria do conduto a jusante de válvula tipo segmento invertida em sistema de enchimento e esvaziamento de eclusas de navegação - Santos, Jessé Baptista Veronese dos (Universidade do Vale do Rio dos Sinos, 2012)
This paper presents a study of fluid dynamic behavior in the operation of inverted Tainter gate, used in filling and emptying systems of navigation locks. In this research is verified the influence of geometric change in the conduit downstream of the gate. The main objective is to find among geometric changes one that offers the best operating condition, i.e., minimizing the harmful effects of low pressures. The study is conducted through numerical approach (CFD-Computer Fluid Dynamics) with the commercial software ANSYS-CFX, using the equations of conservation of mass and momentum as the basic model. Were simulated 3 expansion lengths (Lexp = 0.3, 0.6 and 0.9 m) in the roof of downstream gate, keeping the same slope (1E:10 Lexp, where E is the elevation of the roof). For each expansion length were three simulated stream flow (Q) and 3 openings (a), totaling 27 numerical simulations. Comparisons between the numerical results for the proposed expansions are made from the numerical model (original) previously validated in published works. Also analysis are made of parameters such as geometric changes, minimum pressures, the conduit regions undergoing critical pressures (negative) pressure recovery, pressure loss and contraction coefficients. This analysis allowed observing the influence of the expansion in the flow, showing that the numerical simulation can be used to support the definition of new geometries to be adopted in the design of new navigation locks, as well as evaluation of existing locks, identifying the harmful operating conditions in the region near the gate. It is verified in this work that the geometric changes proposed are not able to solve the problems relating to negative pressures, and its performance depends on operating conditions (mainly the flow). However, the higher the flow rate, the greater the pressures obtained with minimal expansion to the roof. It is hoped that the results obtained can be used as a basis for projects in order to reduce the harmful effects on the valve (as cavitation, vibration, erosion, noise and spasmodic efforts) and disorders that damage the vessels, while operating within the lock.
Keywords: Simulação numérica; CFD; Eclusas; Mecânica dos fluidos; Válvulas tipo segmento invertido; Numerical simulation; Navigation locks; Fluid mechanics; Inverted tainter gate; ACCNPQ::Engenharias::Engenharia Mecânica